Establishment of Reference Intervals for Aldosterone and Renin in Malaysian Community Using Chemiluminescence Immunoassay (CLIA) - Madzlifah, Ahadon; Tay, Siow Phing; Loh, Huai Heng; Arlizan Baizura, Ariffin; Norliza, Samsuri; Liwan, Lasem; Anselm, Su Ting; Chai, Chee Shee (College of Pathologists, 2024)
Introduction: Primary aldosteronism (PA) is the most common cause of secondary hypertension, characterised by elevated plasma aldosterone (PAC) and suppressed renin (PRC) concentrations. There is lack of uniformity in PA diagnostic criteria due to variability in cut off values. PAC and PRC vary between whites, blacks and Hispanics, but there is no data in Asian community. This study aimed to establish reference intervals (RI) of PAC and PRC for our local community. Material and Methods: A total of 301 multi-racial healthy adults aged 19-63 years with equal male-to-female ratio were recruited. They comprised Chinese (40.5%), Borneo Bumiputera (24.3%), Malays (25.9%), mixed heritage (7.6%) and others (1.7%). PAC and PRC were determined using an automated CLIA analyser (Liaison XL). In this study, reference intervals (RI) of PAC (2.35- 26.21 ng/dL) and PRC (5.99-90.27 μIU/mL) differed from manufacturer’s ranges (PAC: 2.21- 35.3 ng/dL, PRC: 4.4-46.1 μIU/mL). PAC and PRC were significantly higher in females (PAC: p<0.001; PRC: p=0.026) and younger adults (<40 years; PAC: p=0.016; PRC: p<0.001), suggesting the need of gender-specific and age-specific RI. Linear regression demonstrated predictors for PAC and PRC were gender and age, respectively. No significant difference of PAC and PRC among different ethnicity (PAC: p=0.203; PRC: p=0.554). Conclusion: To the best of our knowledge, this was the first report of RI for PAC and PRC of a multi-ethnic population in Southeast Asia. The findings enhanced our understanding on the need of appropriate RI in different cohorts of population. Larger population-based future studies are required to investigate the effect of genetic variation on PAC and PRC.